(untitled) (Ameghiniana, 2013)
The auditory region of this genus is compared with +Cardiatherium, and some Caviidae (Cavia, Galea, Microcavia, +Dolicavia, and Pediolagus). The morphology of this region shows differences between Hydrochoeridae and Caviidae, that are considered of value for their identification as different families.